EFFECTS OF ULTRASOUND TREATMENT ON STRUCTURAL, CHEMICAL AND FUNCTIONAL PROPERTIES OF PROTEIN HYDROLYSATE OF RAINBOW TROUT (ONCORHYNCHUS MYKISS) BY-PRODUCTS - MISIR, G.B.; KORAL, S. (Italian Journal of Food Science, 2018)
In this study, the effects of ultrasound treatment on biochemical, physical, structural and functional properties of fish protein hydrolysate of rainbow trout (Oncorhynchus mykiss) by-products were investigated. Enzymatic hydrolysis was conducted by Alcalase 2.4 L, pH 8, 1 h at 60°C, and enzyme/substrate ratio at 0.5%. A probe-type ultrasound was used for ultrasound assisted hydrolysis (UH) process. Higher protein recovery was obtained in UH than in the conventional enzymatic hydrolysis (CH). The highest foaming capacities of CH and UH were measured as 137.5% and 152.5%, respectively (p<0.05). Overall, our data suggest that ultrasound treatment helps to improve the functional properties such as foaming capacity and stability.